Clinical performance of a new prediction rule of systemic loxoscellism. case report: Rendimiento clínico de una nueva regla de predicción del loxoscelismo sistémico. reporte de caso - Pichardo Rodriguez, Rafael Martin de Jesus Pichardo (2021)
Systemic or cutaneous-visceral loxoscelism is the most severe clinical presentation of loxoscelism. Currently there is no validated laboratory diagnostic method that allows us to confirm the presence of this disease in the face of arachneism. However, there is a clinical prediction rule (CPR), which allows us to predict the evolution of a bite towards a systemic condition and which would be useful in emergency rooms. We present the case of a woman who developed the systemic picture of loxoscelism to whom a new CPR was applied for the early detection of systemic loxoscelism, presenting adequate performance for early evaluation in emergency services.